Detection of sleep bruxism: comparison between an electromyographic and electrocardiographic portable holter and polysomnography. (7th January 2014) - Castroflorio, T.; Deregibus, A.; Bargellini, A.; Debernardi, C.; Manfredini, D.
Summary Recent polysomnographic (PSG) studies showed that the sleep bruxism (SB) event is preceded by a sudden shift in autonomic cardiac activity. Therefore, heart rate could be the simplest‐to‐record parameter for use in addition to portable home EMG monitoring to improve the accuracy in automatic detection of SB events. The aim of the study was to compare the detection of SB episodes by combined surface electromyography and heart rate (HR) recorded by a compact portable device (Bruxoff®), with the scoring of SB episodes by a PSG recording. Twenty‐five subjects (14 'probable' bruxers and 11 non‐bruxers) were selected for the study. Each subject underwent the Bruxoff and the PSG recordings during the same night. Rhythmic masseter muscle activities (RMMAs) were scored according to published criteria. Correlation coefficients and the Bland–Altman plots were calculated to measure the correlation and agreement between the two methods. Results showed a high correlation (Pearson's r = 0·95, P < 0·0001) and a high agreement (bias = 0·05) between Bruxoff and the PSG. Furthermore, the receiver operating characteristic curve analysis showed a high sensitivity and specificity of the portable device (92·3% and 91·6%, respectively) when the cut‐off was set at 4 SB episodes per hour according to published criteria. The Bruxoff device showed a good diagnostic accuracy to differentiate RMMA from other oromotor activities. These findings are important in the light of the need for simple and reliable portable devices for the diagnosis of SB both in the clinical and research settings.